Experimental Comparative Study of Feedback Linearized Controller and Proportional Integral Controller of the DC Bus Voltage of Three-phase Shunt Active Power Filter - Ismail Ghadbane; Mohamed Toufik Benchouia (Institute of Advanced Engineering and Science, 2017)
In This paper we present experimental comparative study of feedBack Linearized and Proportional Integral (PI) Controller of the DC bus voltage of three phase shunt Active Power Filter (APF). The FeedBack Linearized and PI controllers are introduced to improve tracking performance characteristics, power quality and minimized consumption of the reactive power. The algorithm used to identify the reference currents is based on the Self Tuning Filter (STF). The firing pulses of the IGBTs inverter are generated using a hysteresis current controller; which is implemented on an analogue card. Finally, the above study, under steady state and transient conditions, is illustrated with signal-flow graphs and corresponding analysis. This study was verified by experimental tests on hardware prototype based on dSPACE-1104. The experimental results show the feasibility and the effectiveness of the designed active filter, associated with Feedback Linearized and PI controllers and are capability in meeting the IEEE 519-1992 recommended harmonic standard limits.